Comparison of birth certificates and hospital-based birth data on pregnancy complications in Los Angeles and Orange County, California. Issue 1 (December 2016) - Haghighat, Nekisa; Hu, Maogui; Laurent, Olivier; Chung, Judith; Nguyen, Peter; Wu, Jun
Abstract Background The incidence of both gestational diabetes mellitus and preeclampsia is on the rise; however, these pregnancy complications may not be systematically reported. This study aimed to examine differences in reporting of preeclampsia and gestational diabetes between hospital records and birth certificate data, and to determine if such differences vary by maternal socioeconomic status indicators. Methods We obtained over 70, 000 birth records from 2001 to 2006 from the perinatal research database of the Memorial Care system, a network of four hospitals in Los Angeles and Orange Counties, California. Memorial birth records were matched to corresponding state birth certificate records and analyzed to determine differential rates of reporting of preeclampsia and diabetes. Additionally, the influence of maternal socioeconomic factors on the reported incidence of such adverse pregnancy outcomes was analyzed. Socioeconomic factors of interest included maternal education levels, race, and type of health insurance (private or public). Results It was found that the birth certificate data significantly underreported the incidence of both preeclampsia (1.38 % vs. 3.13 %) and diabetes (1.97 % vs. 5.56 %) when compared to Memorial data. For both outcomes of interest, the degree of underreporting was significantly higher among women with lower education levels, among Hispanic women compared to Non-Hispanic White women, and among women with public health insurance. Conclusion The Memorial Care database is a more reliable source of information than birth certificate data for analyzing the incidence of preeclampsia and diabetes among women in Los Angeles and Orange Counties, especially for subpopulations of lower socioeconomic status.